Variables Related to Microwave Heating-Toasting Time and Water Migration Assessment with Kernel Size Approaches of Specialty Maize Types - Osorio-Lira, F (John Wiley and Sons Ltd, 2022)
BACKGROUND: Three main maize types with specialty kernels are used to make ready-to-eat maize by traditional toasting, and microwave toasting may be an innovative application. However, little is known of the toasting process of these Andean maize types. Therefore, the present study aimed to explore the behavior of a broad scope of variables in these maize types. The kernels were packed in sealed paper envelopes and subjected to six microwave heating-toasting times from 0 to 390 s. Subsequently, with actual kernel size approaches, water content (WC), water ratio (WR), and water loss (WL) were analyzed. RESULTS: In addition to WC, WR, and WL, the surface area (S), volume (V), and geometric mean diameter (GMD) behaved like time-related variables with a high correlation depending on the maize types and kernel dimensions. Thus, the WC, WR, and WL third-order polynomial regression curves computed with the spatial (S/V)2 and distance (GMD/2)2 approaches indicated the water variation at each microwave heating-toasting time with a clear difference among maize types a0, a1, and a2. Regarding their exchange profiles without and with the spatial (S/V)2 approach, the maximum rates showed significant differences between maize types and WC and WL. Likewise, the maximum rates displayed significant differences between the spatial (S/V)2 and distance (GMD/2)2 approaches, revealing a notable lack of consistency with the distance (GMD/2)2 approach. CONCLUSION: The kernel size approaches revealed that water migration rates depended on differences in maize types. Such basic information represents the first insight into more physical-based models of water diffusion during raw microwave maize heating-toasting. © 2022 Society of Chemical Industry. © 2022 Society of Chemical Industry.